Can social entrepreneurship help attain sustainable development goals: a study of India. (17th March 2020) - Bansal, Sanchita; Garg, Isha; Yadav, Anshita
This paper attempts to understand, analyse and interpret the role of social entrepreneurs towards sustainable development. The paper significantly contributes to the existing literature by evaluating the government's policy framework with respect to social entrepreneurship from the perspective of sustainable development goals (SDGs). The paper also discusses the origin and evolution of social entrepreneurship in India. The paper uses data from various government, non-government and international agency sources for attaining its research objectives. The paper concludes by recommending the policy inputs in respect of social entrepreneurship for ensuring sustainable development in synchronisation with the Sustainable Development Goals.